Women’s Musical Agency and Experiences in Vernon Lee’s Music and its Lovers - Franseen, Kristin (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2017)
Among the case studies included in Vernon Lee’s last book, Music and its Lovers (1933) one finds an intriguing alliance between gender and the experience of listening to instrumental music. A respondent identified only as “The Suffragette” directly ties her feelings about music to her activism, noting that “I recognize in music some definite emotions pertaining to a crowd…the growl I have heard in crowds at suffrage meetings” and later writing about Brahms that “I think I can distinguish in music secondary sex attributes.” Lee notes that the Suffragette, while untrained in music, appears perceptive in linking instrumental music to her personal experiences.While prior research on Music and its Lovers (Towheed 2010 and 2013; Mahoney 2015) has focused primarily on Lee’s sources and questionable scientific practices, this article examines the repertoire and accounts of listening submitted by some of Lee’s female participants. Although Lee’s respondents and ultimate theories of musical emotion cut across gender, her lengthy excerpts from her own experiments center women’s experiences as listeners with valuable observations into the musical experience. In collecting case studies from within her own social circle of women artists and intellectuals, Lee preserved an important archive of early twentieth-century women’s thoughts about specific types of music, especially when it comes to composers traditionally associated with masculinity (Brahms and Beethoven) and sexuality (Tchaikovsky and Wagner).